Disciplines, Sectors, Motivations and Power Relations in Forest Landscape Restoration - Mansourian, S. (University of Wisconsin Press, 2021)
Understanding the diversity of stakeholders involved in large scale forest restoration is essential to its success as restoration is fundamentally about people. Stakeholders may be categorized in different ways, recognizing that categories hide unique differences. When dealing with landscapes or large scales, stakeholders can be found at different spatial scales, and those involved in the restoration action may not necessarily be the ones benefitting or losing the most from restoration. In forest landscape restoration (FLR), each stakeholder may understand the approach differently, engage with it in diverse ways, be motivated by different benefits and may use it for different outcomes. The purpose of this contribution is to better understand how different stakeholders in FLR can be categorized and what motivates them to engage in restoration. Power dynamics among stakeholders shape decision-making related to large scale forest restoration but are often overlooked. Exploring some of the contextual specificities of FLR initiatives helps to define the range of issues associated with such dynamics among stakeholders. I propose to disaggregate ‘stakeholder engagement’ focusing on five dimensions to better understand the different stakeholders engaged in FLR, and then apply it to one case study in Madagascar. Such an approach can support policymakers, project developers and managers, as well as other decisionmakers in designing more effective FLR interventions.